Neutron Beam Characterization on the Beam Tubes of 30 MW G.A. Siwabessy Reactor Using Monte Carlo. Issue 1 (1st August 2022) - Rasito,; Su'ud, Z; Permana, S
Abstract: The neutron beam characterization had been conducted on six tubes of RSG-GAS reactor for BNCT application in a simulation using Monte Carlo method with MCNP computer code. The simulation was conducted by modeling the geometry and material of RSG-GAS reactor with a model of radiation source from 235 U fission reaction in 40 fuel bundles type U3Si2Al with 235 U levels of 19.75%. The distribution of neutron and gamma fluxes was simulated from the reactor core to the edge of beam tube of S1, S2, S3, S4, S5, and S6 with a tube length of 400 cm and a diameter of 30 cm. The highest neutron flux produced by the beam tube of S5 was 4.3×10 10 cm −2 s −1 with the highest gamma dose was 1362 Sv/j. The lowest neutron flux produced by the beam tube of S6 was 5.9×10 9 cm −2 s −1 with a gamma dose was 51 Sv/j. Based on the characterization result, it was shown that the output neutron beam of each RSG-GAS beam tube had the potential to be used for many application.